Mosquito Soldiers : Malaria, Yellow Fever, and the Course of the American Civil War - Bell, Andrew McIlwaine, 1970- (Book collections on Project MUSE., 2010)
Of the 620,000 soldiers who perished during the American Civil War, the overwhelming majority died not from gunshot wounds or saber cuts, but from disease. In this ground-breaking medical history, Andrew McIlwaine Bell explores the impact of two terrifying mosquito-borne maladies--malaria and yellow fever--on the major political and military events of the 1860s, revealing how deadly microorganisms carried by a tiny insect helped shape the course of the Civil War.